Unnatural exposure - Cornwell, Patricia Daniels, 1953- (Kay Scarpetta ;, 1998)
Ireland and Richmond, Virginia: separated by thousands of miles linked by murder. For Dr Kay Scarpetta a lecture stint in Ireland provides the perfect opportunity to find out if the murders on both sides of the Atlantic are indeed connected.Five dismembered, beheaded bodies were found in Ireland years ago now four have been discovered in the States. But the tenth corpse in Virginia is different. There arc vital discrepancies, and an indication that the elderly victim was already seriously ill. A copy-cat killing. Goulish, perhaps, but not unusual. And then abject terror grips Scarpetta and her colleagues when the next body is found. The circumstances of death broadcast a clear and horrifying message: the killer is armed with the most lethal weapon on earth smallpox. 'For all the gory detail Cornwell's novels are oddly comforting. Virtue will out' Frances Fyfield, The Independent 'No one is better than Cornwell at blending the details of leading-edge science and old-fashioned, blood-curdling horror' Vai McDermid, Express on Sunday